Opportunities and Challenges of the Blue Economy in Improving Coastal Economies - Sugeng Siswanto; Heru Subiyantoro; Cicih Ratnasih (Nomico, 2025)
This study investigates the opportunities and challenges of the Blue Economy in improving coastal economies, focusing on the management of marine resources, renewable energy utilization, marine ecosystem quality, sea-based tourism, and technological innovation. The research explores the impact of these factors on the growth and sustainability of coastal economies, with an emphasis on the challenges such as environmental issues, dependence on natural resources, and the need for better infrastructure and community skills. The findings reveal that Blue Economy initiatives can drive significant economic development by promoting sustainable resource management and boosting sectors like fishing, tourism, and renewable energy. The study underscores the importance of strategic policies, collaboration between stakeholders, and the adoption of innovative technologies to maximize the potential of the Blue Economy for coastal communities.